Geraniin Protects High-Fat Diet-Induced Oxidative Stress in Sprague Dawley Rats - Chung, Alexis Panny Y. S.; Gurtu, Sunil; Chakravarthi, Srikumar; Moorthy, Mohanambal; Palanisamy, Uma D. (Frontiers in Nutrition, 2018)
Geraniin, a hydrolysable polyphenol derived from Nephelium lappaceum L. fruit rind, has been shown to possess significant antioxidant activity in vitro and recently been recognized for its therapeutic potential in metabolic syndrome. This study investigated its antioxidative strength and protective effects on organs in high-fat diet (HFD)-induced rodents. Rats were fed HFD for 6 weeks to induce obesity, followed by 10 and 50 mg/kg of geraniin supplementation for 4 weeks to assess its protective potential. The control groups were maintained on standard rat chows and HFD for the same period. At the 10th week, oxidative status was assessed and the pancreas, liver, heart and aorta, kidney, and brain of the Sprague Dawley rats were harvested and subjected to pathological studies. HFD rats demonstrated changes in redox balance; increased protein carbonyl content, decreased levels of superoxide dismutase, glutathione peroxidase, and glutathione reductase with a reduction in the non-enzymatic antioxidant mechanisms and total antioxidant capacity, indicating a higher oxidative stress (OS) index. In addition, HFD rats demonstrated significant diet-induced changes particularly in the pancreas. Four-week oral geraniin supplementation, restored the OS observed in the HFD rats. It was able to restore OS biomarkers, serum antioxidants, and the glutathione redox balance (reduced glutathione/oxidized glutathione ratio) to levels comparable with that of the control group, particularly at dosage of 50 mg geraniin. Geraniin was not toxic to the HFD rats but exhibited protection against glucotoxicity and lipotoxicity particularly in the pancreas of the obese rodents. It is suggested that geraniin has the pharmaceutical potential to be developed as a supplement to primary drugs in the treatment of obesity and its pathophysiological sequels.